Factors Affecting the Effectiveness of Academic Administration in Extended Opportunity Schools under Trat Primary Educational Service Area Office - สุภาสัย ฎีกา; แก้วมงคล ทรงยศ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this study were: 1) to study the level of factors affecting the effectiveness of academic administration 2) to study the level of effectiveness of academic administration 3) to study the relationship between factors affecting the effectiveness of academic administration in extended opportunity schools and 4) to study factors affecting the effectiveness of academic administration in extended opportunity schools under the Trat Primary Educational Service Area Office. A sample size of 193 was determined from school directors and teachers from academic administration in extended opportunity schools under the Trat Primary Educational Service Area Office. The sample size was calculated using the Krejcie-Morgan table at a significance level of .05 and stratified random sampling based on school size. The research instrument was a 5-point rating scale questionnaire. The index of item-objective congruence between 0.80-1.00, The reliability of the questionnaire on factors affecting the effectiveness of academic administration was .931 and on effectiveness of academic administration was .892. Data analysis involved frequency, percentage, mean, standard deviation, Pearson’s product moment correlation coefficient, multiple regression analysis by stepwise and regression equation analysis. The research results were: 1) the level of factors affecting the effectiveness of academic administration in extended opportunity schools were at a high level 2) the level of effectiveness of academic administration in extended opportunity schools were at a high level 3) The analysis of the relationship between factors affecting the effectiveness of academic administration in extended opportunity schools, overall was rated at a relatively low level (rxtotal = .318) at .01 level of significance 4) The predictor variable for the factors affecting the effectiveness of academic administration in extended opportunity schools under the Trat Primary Educational Service Area Office was the factor of attracting. The regression of raw scores and standardized scores were as follows; Y = 2.911 + 0.154 (X5) ZY = 0.298 (ZX5)